Knowledge sharing process for pair programming practice among university students - Zaibon, Syamsul Bahrin; Ahmad, Mazida; Omar, Mazni; Zainol, Azida (2015)
Pair programming practice has been widely used as a pedagogical approach in educational setting specifically in the programming course. Most pair programming studies agree that this practice can foster knowledge sharing among students. However, the studies do not highlight knowledge sharing during pair programming practices and towards their performance. Therefore, the main aim of this study is to test the suitability of knowledge sharing activities by using Socialization, Externalization, Combination, and Internalization (SECI) model in pair programming practices (PPP) amongst students in higher learning institution. In achieving the main aim, this study involved experimentation in order to test the effectiveness of the SECI model. 202 participants were actively engaged in pair programming practices, and involved in the experimentation of the study. The findings reveal that there are significant direct effect of Socialization towards Externalization, Externalization towards Combination and Combination towards Internalization. However, the direct effect of Internalization towards Performance are not significant. In addition, the direct effect of SECI model for pair programming practices are not significant towards the performance of the students.